Salivary Biomarkers for Oral Squamous Cell Carcinoma Diagnosis and Follow-Up: Current Status and Perspectives - Cristaldi, Marta; Mauceri, Rodolfo; Di Fede, Olga; Giuliana, Giovanna; Campisi, Giuseppina; Panzarella, Vera (Frontiers in Physiology, 2019)
Oral cancer is the sixth most common cancer type in the world and 90% of it is represented by Oral Squamous Cell Carcinoma (OSCC). Despite progress in preventative and therapeutic strategies, delay in OSCC diagnosis remains one of the major causes of high morbidity and mortality; indeed the majority of OSCC has been lately identified in the advanced clinical stage (i.e. III or IV). Moreover, after primary treatment, recurrences and/or metastases are found in more than half of the patients (80% of cases within the first two years) and the 5-year survival rate is still lower than 50%, resulting in a serious issue for public health. Currently, histological investigation represents the “gold standard” of OSCC diagnosis; however, recent studies have evaluated the potential use of non-invasive methods, such as “liquid biopsy”, for the detection of diagnostic and prognostic biomarkers in body fluids of oral cancer patients. Saliva is a biofluid containing factors such as cytokines, DNA and RNA molecules, circulating and tissue-derived cells and extracellular vesicles that may be used as biomarkers; their analysis may give us useful information to do early diagnosis of OSCC and improve the prognosis. Therefore, the aim of this review is reporting the most recent data on saliva biomarkers detection in saliva liquid biopsy from oral cancer patients; with particular attention to circulating tumor DNA, extracellular vesicles and microRNAs. Our results highlight that saliva liquid biopsy has several promising clinical uses in OSCC management; it is painless, accessible, low-cost and represents a very helpful source of diagnostic and prognostic biomarker detection. Even if standardized protocols for isolation, characterization and evaluation are needed, the recent data suggest that saliva may be successfully included in the future clinical diagnostic processes, with a considerable impact on early treatment strategies and a favorable outcome.